Obstructive sleep apnea representations, self-efficacy and family coping regarding APAP adherence: a longitudinal study. - Sampaio, Rute; Pereira, M. Graça; Winck, João C. (Psychology, Health & Medicine, 2014)
Adherence is still an important issue considering new advances in Obstructive Sleep Apnea (OSA) treatment, as automatic positive airway pressure (APAP). The aim of the present study was to identify and explore relationships between identified predictors of adherence, over time. After overnight sleep study and OSA diagnosis and during a six-month APAP treatment period, a total of 153 patients underwent a three time psychological protocol evaluation. Generalized estimating equations were applied to analyzed repeated measurements in the same individuals. Results show that 40% of patients were poorly adherent and 60% were adherent after six months of treatment. The results confirmed a predictive value of age, self-efficacy, decisional balance index and health-related quality of life (HRQoL) in APAP adherence. Furthermore, the results revealed an interaction between time and illness cognitive representations, and self-efficacy and family coping, in explaining adherence patterns over time. Therefore, understanding the causality of theoretically derived constructs is crucial to predict the continuity of APAP adherence.